Analysis of Effectiveness Lot Sizing Based on Design of Experiment - Nugraha, Evan; Puspawardhani, Gianti; Norina, Rida (Yayasan Riset dan Pengembangan Intelektual, 2025)
Lot sizing techniques have been widely analyzed by experts, because ordering costs, storage costs, and lot sizes have a significant impact on the total cost of ordering. This study uses lot sizing techniques including Wagner-Whitin algorithm, Silver-Meal algorithm, Least Unit Cost, Least Total Cost, Part Period Balancing, Period Order Quantity, Groff algorithm, and Lot for Lot. The data used is taken from a chemical raw material procurement company, including ordering and storage costs. The initial analysis concluded that the Silver-Meal algorithm and the Groff algorithm have relative biases that are close to the Wagner-Whitin algorithm. The second analysis concluded that for the lot sizing technique, the calculated F value (84.3) was greater than the F table value (2.1), indicating a significant effect of the lot sizing technique on the relative bias percentage. Furthermore, the demand analysis shows that the calculated F value (80.0) is greater than the F table value (2.6), indicating a significant influence of the demand on the percentage relative bias